The ageing population. Issue 5 (May 2021) - Walton, Jenny; Kaye, Angus
As we all age, the demographic of the world changes. Looking after older people well can bring a huge amount of pleasure and satisfaction, not just to the individual, but also to their family, friends and indeed healthcare professionals. How we care for our elderly now is likely to set a precedent for our own care in the future. This article highlights some of the features of ageing and discusses the role of primary care in the management of the older population, within the context of the general practice curriculum.